2001
DOI: 10.1002/jsfa.861
|View full text |Cite
|
Sign up to set email alerts
|

Diferulates as structural components in soluble and insoluble cereal dietary fibre

Abstract: Cell wall cross-linking can have a substantial effect on the properties of the wall. To estimate cross-linking (between arabinoxylans) in cereal ®bres, dehydrodiferulate levels were measured in soluble and insoluble dietary ®bre (SDF and IDF) isolated from whole grains of maize (Zea mays L), wheat (Triticum aestivum L), spelt (Triticum spelta L), rice (Oryza sativa L), wild rice (Zizania aquatica L), barley (Hordeum vulgare L), rye (Secale cereale L), oat (Avena sativa L) and millet (Panicum miliaceum L). Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
225
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(244 citation statements)
references
References 35 publications
(45 reference statements)
8
225
0
2
Order By: Relevance
“…Water-insoluble fibre (IDF) contains lignin, cellulose, hemicelluloses (Bingham 1987;Marlett 1990), and NSP such as water-unextractable arabinoxylan. In millets, NSP form the quantitatively most important source of both soluble and insoluble dietary fibers (Bunzel et al 2001). In cereal botanical components, the majority of dietary fibres generally occur in decreasing amounts from the outer pericarp to the endosperm, except arabinoxylan, which is also a major component of endosperm cell wall materials.…”
Section: Dietary Fiber (Df)mentioning
confidence: 99%
“…Water-insoluble fibre (IDF) contains lignin, cellulose, hemicelluloses (Bingham 1987;Marlett 1990), and NSP such as water-unextractable arabinoxylan. In millets, NSP form the quantitatively most important source of both soluble and insoluble dietary fibers (Bunzel et al 2001). In cereal botanical components, the majority of dietary fibres generally occur in decreasing amounts from the outer pericarp to the endosperm, except arabinoxylan, which is also a major component of endosperm cell wall materials.…”
Section: Dietary Fiber (Df)mentioning
confidence: 99%
“…One understudied class of compounds found in grasses and their hydrolysates is the dehydrodiferulates and compounds derived from them (hereafter all simply termed diferulates) (16,17). In grasses, diferulates are produced by radical dimerization of ferulates that acylate arabinoxylan polysaccharides and function as powerful cell wall cross-linkers (16); derivatives of diferulates are released during the hydrolysis of biomass (16,18,19). At present, the structures of a range of diferulates have been described (16,18), but the biological activities of isolated diferulates (beyond their function in the plant cell wall) have not been explored.…”
mentioning
confidence: 99%
“…The highest diferulic acid contents in cereals were found in popcorn, followed by maize, rye, barley, oats, and wheat (ranging between around 250 and 475 µg/g of flour) (Jilek & Bunzel 2013). Diferulic acids may play an important role in dietary fibre by influencing the chemical structure of dietary fibre components (Bunzel et al 2001). Studies have shown that esterified diferulates can be released from cereals by intestinal enzymes, and that free diferulic acids can be absorbed and enter the circulatory system (Andreasen et al 2001).…”
mentioning
confidence: 99%